The Effect of Ozone Gas Change of Temperature Change Over Iraq - Al-Hamdani, Hussein Jasim Muheisen; Al-Asadi, Kadhim Abdul Wahhab (Journal of Ecohumanism, 2025)
The ozone layer and the ozone gas it carries have become a global issue, and people in different countries of the world are concerned about it due to the dangers it entails and warns of due to its various effects on living organisms on the surface of the Earth, including humans, animals and plants. Given the effect of the ozone layer on temperature rates, which is considered one of the causes of climate change on planet Earth, it has become necessary to know the effect of ozone gas changes on temperature changes over Iraq by analyzing the relationship between ozone gas and temperature rates for selected cities, representing the regions of Iraq, namely Mosul, Kirkuk, Baghdad, Najaf, Wasit, Muthanna and finally Basra. For the period (1989-2022, it represents Iraq’s northern, central, and southern regions.The study’s objective is to determine the correlation between ozone gas concentrations and temperature rates for every month of the year. It has been discovered that there is a negative (inverse) relationship between ozone gas and temperature rates in all months. Higher temperatures are associated with lower ozone concentrations. Depending on the seasons of the year, the relationship also changed. Our observations indicate that the relationship is weak during most winter months, moderate during many spring and autumn months, and strong to very strong during most summer months.